Analysis of the interaction between human RITA and Drosophila Suppressor of Hairless. - Brockmann, B.; Mastel, H.; Oswald, F.; Maier, D. (Hereditas, 2014)
Notch signalling mediates intercellular communication, which is effected by the transcription factor CSL, an acronym for vertebrate CBF1/RBP-J, Drosophila Suppressor of Hairless [Su(H)] and C. elegans Lag1. Nuclear import of CBF1/RBP-J depends on co-activators and co-repressors, whereas the export relies on RITA. RITA is a tubulin and CBF1/RBP-J binding protein acting as a negative regulator of Notch signalling in vertebrates. RITA protein is highly conserved in eumatazoa, but no Drosophila homologue was yet identified. In this work, the activity of human RITA in the fly was addressed. To this end, we generated transgenic flies that allow a tissue specific induction of human RITA, which was demonstrated by Western blotting and in fly tissues. Unexpectedly, overexpression of RITA during fly development had little phenotypic consequences, even when overexpressed simultaneously with either Su(H) or the Notch antagonist Hairless. We demonstrate the in vivo binding of human RITA to Su(H) and to tubulin by co-immune precipitation. Moreover, RITA and tubulin co-localized to some degree in several Drosophila tissues. Overall our data show that human RITA, albeit binding to Drosophila Su(H) and tubulin, cannot influence the Notch signalling pathway in the fly, suggesting that a nuclear export mechanism of Su(H), if existent in Drosophila, does not depend on RITA.